Deconvolution of B cell receptor repertoire in multiple sclerosis patients revealed a delay in tBreg maturation - Lomakin, Yakov A.; Zvyagin, Ivan V.; Ovchinnikova, Leyla A.; Kabilov, Marsel R.; Staroverov, Dmitriy B.; Mikelov, Artem; Tupikin, Alexey E.; Zakharova, Maria Y.; Bykova, Nadezda A.; Mukhina, Vera S.; Favorov, Alexander V.; Ivanova, Maria; et al. (Frontiers in Immunology, 2022)
Background B lymphocytes play a pivotal regulatory role in the development of the immune response. It was previously shown that deficiency in B regulatory cells (Bregs) or a decrease in their anti-inflammatory activity can lead to immunological dysfunctions. However, the exact mechanisms of Bregs development and functioning are only partially resolved. For instance, only a little is known about the structure of their B cell receptor (BCR) repertoires in autoimmune disorders, including multiple sclerosis (MS), a severe neuroinflammatory disease with a yet unknown etiology. Here, we elucidate specific properties of B regulatory cells in MS. Methods We performed a prospective study of the transitional Breg (tBreg) subpopulations with the CD19+CD24highCD38high phenotype from MS patients and healthy donors by (i) measuring their content during two diverging courses of relapsing-remitting MS: benign multiple sclerosis (BMS) and highly active multiple sclerosis (HAMS); (ii) analyzing BCR repertoires of circulating B cells by high-throughput sequencing; and (iii) measuring the percentage of CD27+ cells in tBregs. Results The tBregs from HAMS patients carry the heavy chain with a lower amount of hypermutations than tBregs from healthy donors. The percentage of transitional CD24highCD38high B cells is elevated, whereas the frequency of differentiated CD27+ cells in this transitional B cell subset was decreased in the MS patients as compared with healthy donors. Conclusions Impaired maturation of regulatory B cells is associated with MS progression.